2013
DOI: 10.1371/journal.pone.0073502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Pulmonary Vasodilators on Arterial Saturation in a Model of Pulmonary Hypertension

Abstract: BackgroundApproved therapies for pulmonary arterial hypertension can induce oxygen desaturation when administered to patients with secondary forms of pulmonary hypertension (PH), probably due to an increase in ventilation/perfusion mismatch. Thus, so far these treatments have largely failed in secondary forms of PH.MethodsWe established an animal model of heterogeneous lung ventilation to evaluate the desaturation potential of mechanistically distinct vasoactive drugs launched or currently in clinical developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Therapeutic administration of JSI-124 from day 7 to day 28 of the experimental procedure improved rat pulmonary artery remodelling, right ventricle hypertrophy, PH, ventilation, lung blood perfusion and V/Q mismatching induced by bleomycin. In contrast, bosentan predominantly increased perfusion and in a lesser extent ventilation, showing a mild impairment of V/Q as previously outlined 49. Although results provided in this work relates JAK2 with IPF and PH, it should be noted that human samples used are from no more than 10 patients, a small sample that can limit the interpretation of this work.…”
Section: Discussionmentioning
confidence: 63%
“…Therapeutic administration of JSI-124 from day 7 to day 28 of the experimental procedure improved rat pulmonary artery remodelling, right ventricle hypertrophy, PH, ventilation, lung blood perfusion and V/Q mismatching induced by bleomycin. In contrast, bosentan predominantly increased perfusion and in a lesser extent ventilation, showing a mild impairment of V/Q as previously outlined 49. Although results provided in this work relates JAK2 with IPF and PH, it should be noted that human samples used are from no more than 10 patients, a small sample that can limit the interpretation of this work.…”
Section: Discussionmentioning
confidence: 63%
“…Pulmonary vasodilators have been associated with hypoxemia due to attenuation of hypoxic pulmonary vasoconstriction (Euler‐Liljestrand mechanism) and an increase in intrapulmonary shunts . This effect has been confirmed in animal models of heterogeneous lung ventilation and should be considered in infants with a ventilation‐perfusion mismatch .…”
Section: Discussionmentioning
confidence: 88%
“…For riociguat, our results contrast with previous studies where systemic vasodilation with decreased SVR and MAP at similar doses were observed. 14,22,23,28 Sildenafil has previously been shown to induce systemic vasodilation and hypotension. 29 Sildenafil did not cause a significant reduction in systemic blood pressure in this study, but this should be taken with caution due to the small sample size.…”
Section: Effects Of No-sgc-cgmp Stimulationmentioning
confidence: 99%
“…This indicates that NO-sGC-cGMP stimulation did not worsen the ventilation/ perfusion mismatch as a result of increased intrapulmonary shunting -an adverse effect reported in experimental studies and clinical cases. 4,28,35,36 The potential for improvement in respiratory parameters was limited by the only mild respiratory impairment of this model. Since hypoxia was avoided, the pulmonary vasodilatory effects found in the present study can be attributed directly to NO-sGC-cGMP vascular stimulation and not to attenuation of hypoxia or hypercapnia.…”
Section: Effects Of No-sgc-cgmp Stimulationmentioning
confidence: 99%